2017
DOI: 10.1590/1981-6723.4016
|View full text |Cite
|
Sign up to set email alerts
|

Sensory profile and evaluation of the degree of acceptability of bread produced with inulin and oligofructose

Abstract: Homemade bread was produced with 4.4 and 4.45 g of total fructans per 50 g serving to meet Brazilian standards for prebiotic claims. The bread samples were characterized for their sensory profiles using descriptive analysis and for their sensory acceptability using hedonic and just-about-right scales for sweetness intensity. The sensory profiles of the breads were similar and sweetness was the term that discriminated the bread samples obtained, since the intensity decreased from the bread formulated with oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Water trapped by fibre and hydrocolloids is more readily released via freezing than water associated with gluten networks, resulting in a drier thawed product 37 . The denseness of the breads could be attributed to the underdevelopment of the gluten network due to the incorporated seaweeds 29 and their increased fibre 38 . The attributes of strong aftertaste and saltiness were previously identified in seaweed by Peinado et al 3 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Water trapped by fibre and hydrocolloids is more readily released via freezing than water associated with gluten networks, resulting in a drier thawed product 37 . The denseness of the breads could be attributed to the underdevelopment of the gluten network due to the incorporated seaweeds 29 and their increased fibre 38 . The attributes of strong aftertaste and saltiness were previously identified in seaweed by Peinado et al 3 .…”
Section: Resultsmentioning
confidence: 93%
“…37 The denseness of the breads could be attributed to the underdevelopment of the gluten network due to the incorporated seaweeds 29 and their increased fibre. 38 The attributes of strong aftertaste and saltiness were previously identified in seaweed by Peinado et al 3 Seaweeds have unique chemical compositions that can affect sensory perceptions, depending on the species, season, or surrounding environment. 39,40 Differences in seaweed composition could explain one possible reason for the stronger taste of seaweed associated attributes was found in the C. crispus bread.…”
Section: Sensory Analysismentioning
confidence: 98%
“…The sensory analysis was carried out as described by Souza‐Borges and Conti‐Silva (2018). The bread samples were cooled for three hours to room temperature before serving to an untrained sensory panel (7 males, 8 females) composing of 15 consumers.…”
Section: Methodsmentioning
confidence: 99%
“…Studies [9,10] have shown the promise of using flour from chicory, as a source of inulin, in the technology of gluten-free bread. It is noted that the addition of chicory flour allows not only to improve the functional properties of the product, but also to prolong its freshness.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%